Uruguay : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2006)
This report includes five background studies with emphasis on vulnerabilities and growth, the focus of the 2006 Article IV Consultation with Uruguay. Stocks of key financial balance sheet vulnerabilities are also discussed. With the appreciation of the peso since early 2004, the discussion on competitiveness has intensified. To assess competitiveness, the paper looks at balance of payments trends, the ratio of tradable to nontradable prices, cost and profitability measures, and real exchange rates and their alignment with purchasing power parity (PPP).
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet